The Visual Students’ Problems in Listening Class at the Third Semester Students of IAIN MADURA - Isrok Wulandari; Kristanti Ayuanita (Institut Agama Islam Negeri Madura, 2019)
All of the students that have different learning style learn in listening class include the visuals students. This research investigates: how the visual students learn in listening class at the third-semester students of IAIN Madura (Previously STAIN Pamekasan) and what kind of difficulties faced by visual students in listening class and what factors that make the visual students difficult to comprehend the material in listening class. This is qualitative research. The researcher obtained the data through observation, interview and documentation. The results of this research are the visual students in listening class like doodle and some of them like movies. The difficulties faced by the visual students in listening class are: difficult to answer the question directly and difficult to concentrate when they listened the material. The most factor that makes the visual students difficult to comprehend the material because the situation is crowded. From this research, it is also found that not all of the visual students in listening class like watch movies have a problem or difficult with the verbal or oral instruction, they loss their concentration and can learn in the noise or crowded situation of listening class.